PENDAMPINGAN SISWA DALAM MENINGKATKAN KEMAMPUAN LITERASI AL-QUR’AN DENGAN METODE TILAWATI DI SD IT AL QONITA - Abdul Wahid; Sulistyowati (Universitas Nias Raya, 2024)
Quran education is an important aspect in the development of a Muslim's personality and spirituality. Effective learning is necessary for maximum understanding and mastery of the Quran. This study aims to analyse student support in learning the Tirawati method at SDIT Al-Konita which is used to improve the ability to read the Quran. The Thilawati method is an approach that combines classical habituation techniques with a balanced personal system, emphasising the correct reading and understanding of tajweed and Makraj. This study used participatory action research (PAR) method where teachers, students, and support team participated in planning, implementing, and evaluating the learning process. The results showed that intensive learning successfully improved students' Quran reading skills, resulting in significant improvements in reading fluency and memorisation accuracy. The funding created an interactive and collaborative learning atmosphere, which had a positive impact on students' motivation and interest in learning the Quran. Despite challenges such as students' different learning speeds and time constraints, solutions such as splitting groups and increasing time have been effective. This programme has contributed significantly to the success of Al-Quran learning at SDIT Al-Konita and can be a model for other Islamic educational institutions that best apply the Tilawati Method.